Effect of Vitamin D Supplementation on High Fat Diet Induced Thyroid Dysfunction an RCT on Mouse Model - Chaman Nasrullah, Maimona Tabbsum, Maimoona Nasreen, Saman Saeed Ansari, Hafiza Hina Pasha (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Excess of dietary fats induce hyperlipidemia which causes endoplasmic reticulum (ER)stress. ER stress causes thyroid dysfunction and reduces serum thyroid hormone levels. Vitamin D supplementation increases thyroid hormone levels by reducing high fat diet induced ER stress, inflammation and autoimmunity. Objective: This study was planned to determine the effect of vitamin D supplementation on levels of serum free and total thyroxine in male albino mice. Methodology: In this randomized control trial, ninety healthy male albino mice were taken by consecutive, nonprobability sampling and randomly divided into three groups, each group containing 30 mice. Group A mice were given normal diet, Group B mice were given high fat diet, Group C mice were given high fat diet and vitamin D through oral gavage (100ng/kg/day) for 6 weeks. By the end of 6 weeks, blood sample of all mice was taken by cardiac puncture and serum was separated. Levels of serum total thyroxine and free thyroxine were measured by ELISA technique. Data was analyzed by using SPSS version 20. Results: In group B mice (high fat diet group) serum total and free thyroxine levels were reduced significantly (p=0.00) as compared to group A mice (normal diet group). In group C mice (high fat diet plus vitamin D group) serum total and free thyroxine levels were increased significantly (p=0.00) as compared to group B mice ( high fat diet group). The results of group C and A were also comparable and significant, with serum free and total thyroxine levels significantly high in group C (high fat diet+ vitamin D) as compared to group A(normal diet). Conclusion: Vitamin D supplemented mice on high fat diet had increased levels of serum total thyroxine, free thyroxine as compared to the group of mice on high fat diet only. Keywords: Vitamin D, High fat diet, Hyperlipidemia, Thyroxine.